Theophrastus of Eresus : sources for his life, writings, thought and influence. Commentary volume 5, Sources on biology (Human physiology, living creatures, botany : texts 328-435) - Sharples, R. W. (Philosophia Antiqua, 1994)
This is the first to appear of the projected volumes of commentary to accompany the texts and translations on Theophrastus of Eresus: Sources for his Life, Writings, Thought and Influence , edited by W.W. Fortenbaugh and others (\'FHSG\' (Philosophia Antiqua 54); Leiden, Brill, 1992). It covers the ancient secondary evidence for Theophrastus' views on physiology, zoology and botany; the transmission, reliability and doctrinal content of the reports in the text-and-translation volume are all discussed in detail, and general overviews are provided. The commentary is an indispensable accompaniment to the text-and-translation volume, and the two together will be an important resource for students of the history of the biological sciences in antiquity.